2013
DOI: 10.1111/pde.12162
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Later Presentations of Venous Malformations: Where and Why?

Abstract: Venous malformations (VMs) are congenital anomalies of the venous vasculature, but not all are evident at birth. The factors that lead to presentation later in life are not well understood. The objective of this retrospective cohort study of patients with VMs evaluated at the University of California at San Francisco Birthmarks and Vascular Anomalies Center from 2005 to 2009 was to investigate the clinical presentation of VMs and correlate these features with different types of tissues (e.g., skin, subcutis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…This exercise-limiting pain essentially nullifies the normal compressibility one would expect of intramuscular lesions. In fact, Vogel et al [15] demonstrated that intramuscular venous malformations contained more phleboliths than lesions involving other tissue types further supporting this low flow hypothesis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This exercise-limiting pain essentially nullifies the normal compressibility one would expect of intramuscular lesions. In fact, Vogel et al [15] demonstrated that intramuscular venous malformations contained more phleboliths than lesions involving other tissue types further supporting this low flow hypothesis.…”
Section: Discussionmentioning
confidence: 87%
“…On first glance, intramuscular venous malformation association with LIC would appear to contradict the theory that lack of compression leads to an abnormality in the coagulation cascade. Intramuscular venous malformations, however, tend to be more painful than lesions involving other tissue types and this pain is severe enough to limit exercise and otherwise normal activity [15,16]. This exercise-limiting pain essentially nullifies the normal compressibility one would expect of intramuscular lesions.…”
Section: Discussionmentioning
confidence: 96%
“…Our patients developed symptoms from infancy to adolescence, similar to other VM cohorts . VMs worsen over time, particularly around puberty .…”
Section: Discussionmentioning
confidence: 99%
“…They may be evident at birth, but many cases, particularly those with predominantly intramuscular disease, often present later in life with pain provoked by vigorous physical activity. 45 Familial VMs present generally as small…”
Section: Simple Vascular Malformationsmentioning
confidence: 99%